Sin, Sex and Democracy: Politics and the Catholic Church - Lecaros, Véronique (2023)
This examination of seemingly unrelated concepts—sin, sex and democracy; politics and the Catholic Church—illuminates areas of tension and debate that scholars have explored, yet demand further nuanced and thorough exploration. In this discussion, we outline two main lines of inquiry. The first involves a more conventional exploration of the interplay between democracy and the concepts of truth and sin. The second delves into a contemporary examination of the challenges confronting the Catholic Church in the wake of the sexual abuse crisis and of the Church’s efforts to establish practices of democratic accountability within a framework not ruled by democratic principles.